Mesenchymal stem cells loaded on 3D-printed gradient poly(ε-caprolactone)/methacrylated alginate composite scaffolds for cartilage tissue engineering. Issue 3 (16th May 2021) - Cao, Yanyan; Cheng, Peng; Sang, Shengbo; Xiang, Chuan; An, Yang; Wei, Xiaochun; Shen, Zhizhong; Zhang, Yixia; Li, Pengcui
Abstract: Cartilage has limited self-repair ability due to its avascular, alymphatic and aneural features. The combination of three-dimensional (3D) printing and tissue engineering provides an up-and-coming approach to address this issue. Here, we designed and fabricated a tri-layered (superficial layer (SL), middle layer (ML) and deep layer (DL)) stratified scaffold, inspired by the architecture of collagen fibers in native cartilage tissue. The scaffold was composed of 3D printed depth-dependent gradient poly(ε-caprolactone) (PCL) impregnated with methacrylated alginate (ALMA), and its morphological analysis and mechanical properties were tested. To prove the feasibility of the composite scaffolds for cartilage regeneration, the viability, proliferation, collagen deposition and chondrogenic differentiation of embedded rat bone marrow mesenchymal stem cells (BMSCs) in the scaffolds were assessed by Live/dead assay, CCK-8, DNA content, cell morphology, immunofluorescence and real-time reverse transcription polymerase chain reaction. BMSCs-loaded gradient PCL/ALMA scaffolds showed excellent cell survival, cell proliferation, cell morphology, collagen II deposition and hopeful chondrogenic differentiation compared with three individual-layer scaffolds. Hence, our study demonstrates the potential use of the gradient PCL/ALMA construct for enhanced cartilage tissue engineering.